2016
DOI: 10.1098/rspa.2016.0338
|View full text |Cite
|
Sign up to set email alerts
|

A physical model for low-frequency electromagnetic induction in the near field based on direct interaction between transmitter and receiver electrons

Abstract: A physical model of electromagnetic induction is developed which relates directly the forces between electrons in the transmitter and receiver windings of concentric coaxial finite coils in the near-field region. By applying the principle of superposition, the contributions from accelerating electrons in successive current loops are summed, allowing the peak-induced voltage in the receiver to be accurately predicted. Results show good agreement between theory and experiment for various receivers of different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that it is consistent with Maxwell's equations [54][55][56][57][58]. Research into Weberian electrodynamics has received a significant contribution from Assis [38,55,[59][60][61] and has been applied to several pure and applied problems [43,52,57,[62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 92%
“…It has been demonstrated that it is consistent with Maxwell's equations [54][55][56][57][58]. Research into Weberian electrodynamics has received a significant contribution from Assis [38,55,[59][60][61] and has been applied to several pure and applied problems [43,52,57,[62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 92%
“…Voltage (U) on the induction coil of unit B resulted from the excitation of oscillations of magnetic nanoparticles in the target area of the medium under the action of ultrasonic radiation. Accordingly to the Faraday's law on electromagnetic induction, the resulting U should be proportional to the magnitude of the nanoparticles' total magnetic field at the detector's location and their speed relative to the detector 12 . In turn, field Ha and U are proportional to the concentration (K) of the nanoparticles in the moving solution.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the forces between steady currents and motional electromagnetic induction are identified with the velocity terms in the Weber force formula, while transformer induction is explained through the acceleration terms [13]. Finally, such an approach has potential advantages in a number of fields such as applied electromagnetics [14], and charge particle dynamics [15,16].…”
Section: Resultsmentioning
confidence: 99%